The Lived Experiences of Non-face-to-face Psychiatric Nursing Practice among Nursing Students: A Parse research Method study - Kang, Gyun-Young; Kim, Jinju (International Journal of Membrane Science and Technology, 2023)
This study is a qualitative study to clarify meaning and structure of lived experiences of non-face-to-face psychiatric nursing practice among nursing student by applying Parse research method. The research question was Would you tell me about your experience of non-face-to-face psychiatric nursing practice? which was examined based on Parse's research method. Participants were 10 nursing students at a community central region of South Korea. As a result, the core concept of lived experiences of non-face-to-face psychiatric nursing practice among nursing student is as follows; Expanding awareness of self and other understanding, Preparation of communication for the formation of therapeutic relationships, Perspective through exploring the meaning of nursing.